STRATEGI GURU DALAM MENGELOLA PERILAKU ATTETION SEEKING PADA SISWA KELAS II DI SDN 14 TANGKALASI - Hidayah; Abrina Maulidnawati; Nur Afni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Attention-seeking behavior is one of the disruptive behaviors often exhibited by elementary school students, particularly in lower grades. This study aims to describe the forms of attention-seeking behavior displayed by second-grade students at SDN 14 Tangkalasi and to analyze the strategies used by teachers to manage such behavior. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The subjects of this study were second-grade teachers and students who showed attention-seeking behavior. The findings reveal that attention-seeking behaviors manifest in various forms, including calling out loudly, disturbing friends, making excessive noise, and displaying exaggerated emotions. The strategies implemented by teachers include: (1) positive reinforcement and praise for appropriate behavior, (2) planned ignoring of minor disruptive behaviors, (3) providing individual attention at scheduled times, (4) assigning special responsibilities to the students, and (5) collaborating with parents and the school counselor. These strategies proved effective in reducing the frequency and intensity of attention-seeking behavior, thereby creating a more conducive learning environment. This study recommends that teachers consistently apply a combination of preventive, supportive, and corrective strategies to address attention-seeking behavior effectively.